Human metapneumovirus associated with facial nerve paralysis - Myers, Chris; Brown, Jason; Arnold, Michelle G.; Arnold, John C. (Journal of Pediatric Neurology, 2011)
Facial nerve paralysis in childhood is commonly caused by acute ear infections and Lyme disease. A number of respiratory viruses have also been associated with acute facial nerve weakness. First described as a common cause of respiratory infection in 2001, human metapneumovirus has now also been associated with abnormalities of the central nervous system, such as seizures and encephalitis. We describe a case of acute facial nerve palsy in which human metapneumovirus was the only pathogen identified, using sophisticated molecular diagnostics.
Keywords: Human metapneumovirus; facial nerve palsy; rapid diagnostics; resequencing microarray